Strategi Pengembangan Destinasi Wisata Sendang Biru Kabupaten Malang - Rudi Santoso (Majalah Ekonomi, 2024)
The research aims to develop a strategy for developing Sendang Biru marine tourism to increase the number of visits. Apart from the long distance, information about Sendang Biru beach is still very minimal. This research is qualitative research using a descriptive approach. Research sources or informants in this research are tourism managers, regional stakeholders, business actors, visitors, and the people of the Sendang Biru region, South Malang. The results of the research provide recommendations in the form of a strategy model that focuses on improving human resources, mapping business types, increasing access to health and education (hospitality), forming business groups engaged in educational tourism, and implementing social media for strategic branding. This research also found the fact that there was an increase in visitors' impressions and awareness of tourist attractions based on the results of social media assessments and evaluations.